Tháng Năm 19, 2024

Rút gọn \(B\). A \(B = \frac{{\sqrt x + 1}}{{\sqrt x – 1}}\) B \(B = \frac{{\sqrt x – 1}}{{\sqrt x + 1}}\) C \(B = \frac{1}{{\sqrt x + 1}}\) D \(B = \frac{1}{{\sqrt x – 1}}\)

Rút gọn \(B\).

A \(B = \frac{{\sqrt x + 1}}{{\sqrt x – 1}}\)

B \(B = \frac{{\sqrt x – 1}}{{\sqrt x + 1}}\)

C \(B = \frac{1}{{\sqrt x + 1}}\)

D \(B = \frac{1}{{\sqrt x – 1}}\)

Hướng dẫn Chọn đáp án là: B

Phương pháp giải:

Qui đồng, khử mẫu và rút gọn.

Lời giải chi tiết:

Điều kiện : \(x \ge 0,\,\,\,x \ne 1.\)

\(\begin{array}{l}B = \frac{{\sqrt x }}{{\sqrt x – 1}} + \frac{3}{{\sqrt x + 1}} + \frac{{6\sqrt x – 4}}{{1 – x}}\\\,\,\,\, = \frac{{\sqrt x }}{{\sqrt x – 1}} + \frac{3}{{\sqrt x + 1}} – \frac{{6\sqrt x – 4}}{{\left( {\sqrt x – 1} \right)\left( {\sqrt x + 1} \right)}}\\\,\,\, = \frac{{\sqrt x \left( {\sqrt x + 1} \right) + 3\left( {\sqrt x – 1} \right) – 6\sqrt x + 4}}{{\left( {\sqrt x – 1} \right)\left( {\sqrt x + 1} \right)}}\\\,\,\, = \frac{{x + \sqrt x + 3\sqrt x – 3 – 6\sqrt x + 4}}{{\left( {\sqrt x – 1} \right)\left( {\sqrt x + 1} \right)}}\\\,\,\, = \frac{{x – 2\sqrt x + 1}}{{\left( {\sqrt x – 1} \right)\left( {\sqrt x + 1} \right)}} = \frac{{{{\left( {\sqrt x – 1} \right)}^2}}}{{\left( {\sqrt x – 1} \right)\left( {\sqrt x + 1} \right)}}\\\,\,\, = \frac{{\sqrt x – 1}}{{\sqrt x + 1}}.\end{array}\)

Vậy \(B = \frac{{\sqrt x – 1}}{{\sqrt x + 1}}\) với \(x \ge 0;\,\,x \ne 1\).

Chọn B.